Research on the move: exploring WhatsApp as a tool for understanding the intersections between migration, mobility, health and gender in South Africa - Thea de Gruchy; Jo Vearey; Calvin Opiti; Langelihle Mlotshwa; Karima Manji; Johanna Hanefeld (BMC, 2021)
Abstract Background Reflecting global norms, South Africa is associated with high levels of cross-border and internal population mobility, yet migration-aware health system responses are lacking. Existing literature highlights three methodological challenges limiting the development of evidence-informed responses to migration and health: (1) lack of engagement with the process of migration; (2) exclusion of internal migrants; and (3) lack of methodologies that are able to capture 'real-time' data about health needs and healthcare seeking experiences over both time and place. In this paper, we reflect on a four-month pilot project which explored the use of WhatsApp Messenger - a popular mobile phone application used widely in sub-Saharan Africa - and assessed its feasibility as a research tool with migrant and mobile populations in order to inform a larger study that would address these challenges. Method A four-month pilot was undertaken with eleven participants between October 2019 and January 2020. Using Survey Node, an online platform that allows for the automatic administration of surveys through WhatsApp, monthly surveys were administered. The GPS coordinates of participants were also obtained. Recruited through civil society partners in Gauteng, participants were over the age of 18, comfortable engaging in English, and owned WhatsApp compatible cell phones. Enrolment involved an administered survey and training participants in the study protocol. Participants received reimbursement for their travel costs and monthly cell phone data. Results Out of a possible eighty eight survey and location responses, sixty one were received. In general, participants responded consistently to the monthly surveys and shared their location when prompted. Survey Node proved an efficient and effective way to administer surveys through WhatsApp. Location sharing via WhatsApp proved cumbersome and led to the development of a secure platform through which participants could share their location. Ethical concerns about data sharing over WhatsApp were addressed. Conclusions The success of the pilot indicates that WhatsApp can be used as a tool for data collection with migrant and mobile populations, and has informed the finalisation of the main study. Key lessons learnt included the importance of research design and processes for participant enrolment, and ensuring that the ethical concerns associated with WhatsApp are addressed.